A propagation-based fault detection and discrimination method and the optimization of sensor deployment. (February 2022) - Li, Boyuan; Diao, Xiaoxu; Vaddi, Pavan Kumar; Gao, Wei; Smidts, Carol
Highlights: A propagation-based fault detection and discrimination method is proposed. Fault diagnosis strategies in steady states and transient states are derived. Optimization of sensor deployment in the design phase is studied. A brute force algorithm and a genetic algorithm is developed for sensor deployment. The methods are verified using the GOTHIC model of EBR-II. Abstract: Industrial processes can be affected by faults having a serious impact on operation when not promptly detected and diagnosed. In this paper, a propagation-basedfaultdetectionanddiscrimination(PFDD) method is proposed to develop a strategy for fault diagnosis while in the design phase of a system. The PFDD method constructs the system model using the IntegratedSystemFaultAnalysis(ISFA) technique. Based on the system model, the propagation of hardware and software faults are simulated qualitatively. Given the results of the simulation, the process by which a fault propagates can be characterized using the qualitative features of system variables including the deviation of the system variables from their expected values, the variation of the system variables over time, and the order in which each variable is influenced during the propagation of the fault. The strategy by which a fault can be detected and discriminated is defined using those features. The PFDD method supports the detection and discrimination of faults in both steady states and transient states. Based on the PFDD method, the optimization of sensor deployment in a system is discussed. A brute force algorithm is developed to examine the system's capability at diagnosing faults and the cost of sensor deployment for all possible configurations of sensors. The optimal sensor deployment strategy can be derived accordingly. However, the brute force method is only applicable to small-scale systems due to its high computational cost. A genetic algorithm is used to optimize sensor deployment in large-scale systems. The PFDD and sensor deployment optimization methods are applied to the Experimental Breeder Reactor II (EBR-II) for verification.